EFFECT OF FLYWHEEL WARM-UP ON LOWER BODY MUSCLE PERFORMANCE IN YOUTH ATHLETES - Liam Younger; Darryl Cochrane (Journal of Applied Sports Sciences)
Post-activation performance enhancement (PAPE) is a phenomenon that has been used as a warm-up strategy to enhance subsequent muscular performance. The purpose of this study was to examine the efficacy of a flywheel warm-up to elicit a PAPE effect in eight male youth rugby athletes. Participants completed three warm-up interventions (flywheel, stationary cycle, and no warm-up) across three days, each separated by 24 hours. A 5-minute rest followed each warm-up before assessing posterior chain flexibility, countermovement jump (CMJ), and linear acceleration. The results showed a significant increase (p < .05) in poste- rior chain flexibility and 10 m sprint performance following the flywheel warm- up compared to stationary cycling and no warm-up. However, the interventions had no significant differences in CMJ peak power or jump height (p > .05). The current findings suggest that the flywheel warm-up is effective in improving pos- terior chain flexibility and sprint performance in youth rugby players.